Promoting Biodiversity, Sustainability and Food Security Through Ancestral Ibero-American Crops: Abstracts of the 6th Ia ValSe-Food Network International Congress - Chasquibol Silva, Nancy Ascención (2024)
Th is congress was organized by the Ia ValSe-Food Group (Ibero-American Valuable Seeds), the Institute of Agrochemistry and Food Technology, Spanish National Research Council (CSIC), Spain, and the University of Lima, Peru. Andean grains are globally recognized for their high nutritional value, well-balanced composition of proteins, fats, and starches, as well as their rich content of essential amino acids, essential fatty acids, and nutraceutical properties. Th ey represent not only a valuable cultural heritage rooted in the ancestral communities of Latin American countries but also a source of solutions to contemporary challenges such as healthy eating and the development of new foods that are low in calories, fats, and sugars. Th e I a ValSe-Food Network is aware of the signifi cance of Andean grains and their role in promoting food security, biodiversity conservation, and climate change resilience